(untitled) (Revista Espinhaço, 2022)
Environmental changes caused by human pressures are the main responsible for biodiversity loss. e conservation and monitoring of remaining natural areas are fundamental to guarantee the provision of resources and ecosystem services to humanity. is study aimed to answer: Surrounded by mining areas and immersed in the anthropogenic matrix of the Doce River basin, does the Caraça River preserve ecological characteristics as a reference ecosystem? Our samplings were conducted in five sites in the Caraça River, located in the Reserva Particular do Patrimônio Natural Santuário do Caraça, Catas Altas (MG). We applied three ecological approaches: Rapid Assessment Protocol for habitat diversity and integrity of riparian zones; measurementof physical and chemical parameters; and sampling of benthic macroinvertebrates. e results confirmed that the Caraça Riverhas well-preserved ecological conditions, good water quality, and high diversity of macroinvertebrates. erefore, despite the heavily disturbed condition caused by mining, agriculture, and urban waste in the Doce River basin, the Caraça River preserves characteristics of an ecosystem in reference conditions for studies of ecological quality, ecological integrity, and environmental monitoring. In summary, the Caraça River offers appropriate conditions for biodiversity conservation, leisure, and human wellbeing, including ecological and religious tourism attractions.